A Review on Anti-Tumor Mechanisms of Coumarins - Wu, Yi; Xu, Jing; Liu, Yiting; Zeng, Yiyu; Wu, Guojun (Frontiers in Oncology, 2020)
Coumarins are a class of compound with benzopyrone as their basic structure. Due to abundant sources, easy synthesis and various pharmacological activities, coumarins have attracted extensive attention from researchers. In particular, coumarins have very significant anti-tumor abilities and a variety of anti-tumor mechanisms, including inhibition of carbonic anhydrase, targeting PI3K/Akt/m - TOR signaling pathways, inducing cell apoptosis protein activation, inhibition of tumor multidrug resistance, inhibition of microtubule polymerization, regulating the reactive oxygen species and inhibition of tumor angiogenesis, etc. This review focuses on the mechanisms and the research progress of coumarins against cancers in recent years.